Outcome in very preterm infants: a population-based study from a regional center in Austria - Konzett, Karin; Riedl, David; Blassnig-Ezeh, Anya; Gang, Stefanie; Simma, Burkhard (Frontiers in Pediatrics, 2024)
Aim: To determine short-term morbidity and mortality rates in the first state-wide Austrian neonatal cohort and comparison to (inter)national data. Methods: Observational, population-based cohort study, analyzing data of preterm infants (< 32+0 weeks of gestation) born between 2007 – 2020 (n=501) in an Austrian state who were admitted to the neonatal intensive care unit. Outcome criteria were mortality, neonatal morbidities: bronchopulmonary dysplasia (BPD), severe necrotizing enterocolitis (NEC), severe intraventricular hemorrhage (IVH grades III-IV), severe retinopathy of prematurity (ROP grades III-V) and survival-free of major complications. Results: Overall survival rate was 95%, survival free of major complications was 79%. Prevalence for BPD was 11.2%, surgical NEC 4.0%, severe IVH 4.6%, and for severe ROP 2.6%%, respectively. In the extremely low gestational age neonates (ELGAN) born <28 weeks of gestation (n=158), survival was 88% and survival free of major complications 58.8%. Over time, mortality decreased significantly, predominantly driven by the improvement of infants born <28 week of gestation and survival free of major complications improved. Conclusions: This study demonstrates a very low mortality rate that decreases over time. Short-term morbidities and survival free of major complications do not differ from (inter)national data in a similar group of very preterm infants. Standard operating procedures, simulation trainings and accordance to international trials may improve patient care and surpass center case loads.